Peningkatan Fungsi Pengawasan DPRD Melalui Penyebarluasan/Sosialisai Peraturan Daerah Provinsi DKI Jakarta Nomor 2 Tahun 2018 Tentang Perpasaran - Ofis Rikardo (Abdi Bhara, 2023)
Regional regulations are a type of statutoryregulation contained in the Indonesian legal system. Theformation of regional regulations must not conflict with higherregulations, namely the UUD 1945, TAP MPR, and UU/Perpu.DKI Jakarta Provincial Government Regional RegulationNumber 2 of 2018 concerning Markets is a progressive step inregulating markets in DKI Jakarta where previously there was aRegional Regulation that regulated the same thing, namelyRegional Regulation Number 2 of 2002. After sixteen years havepassed there have been changes to the structure society'seconomy and its supporting laws and regulations. So thepresence of Regional Regulation Number 2 of 2018 is a step thatshould be appreciated in advancing the economy in markets inDKI Jakarta. Regional Regulation Number 2 of 2018 is here toprovide market regulations that are more integrated, equal andfair in an effort to create fashion certainty and balancedcooperative relationships between suppliers and retailers whilestill paying attention to the alignment of cooperatives, as well asmicro, small and medium enterprises.